A flow-proteometric platform for analyzing protein concentration (FAP): Proof of concept for quantification of PD-L1 protein in cells and tissues - Chou, Chao-Kai; Huang, Po-Jung; Tsou, Pei-Hsiang; Wei, Yongkun; Lee, Heng-Huan; Wang, Ying-Nai; Liu, Yen-Liang; Shi, Colin; Yeh, Hsin-Chih; Kameoka, Jun; Hung, Mien-Chie (Biosensors & bioelectronics, 2018)
Protein expression level is critically related to the cell physiological function. However, current methodologies such as Western blot (WB) and Immunohistochemistry (IHC) in analyzing the protein level are rather semi-quantitative and without the information of actual protein concentration. We have developed a microfluidic technique termed a “flow-proteometric platform for analyzing protein concentration (FAP)” that can measure the concentration of a target protein in cells or tissues without the requirement of a calibration standard, e.g., the purified target molecules. To validate our method, we tested a number of control samples with known target protein concentrations and showed that the FAP measurement resulted in concentrations that well matched the actual concentrations in the control samples (coefficient of determination [R2], 0.998), demonstrating a dynamic range of concentrations from 0.13 to 130 pM of a detection for 2 min. We successfully determined a biomarker protein (for predicting the treatment response of cancer immune check-point therapy) PD-L1 concentration in cancer cell lines (HeLa PD-L1 and MDA-MB-231) and breast cancer patient tumor tissues without any prior process of sample purification and standard line construction. Therefore, FAP is a simple, faster, and reliable method to measure the protein concentration in cells and tissues, which can support the conventional methods such as WB and IHC to determine the actual protein level. •An automatic microfluidic platform to digitally quantify target protein.•Protein concentrations can be measured without a standard.•Automatic quantification of PD-L1 in cancer cells and patient tumor tissues.